Differences in greeting behaviour towards humans with varying levels of familiarity in hand-reared wolves (Canis lupus) - Dorottya Júlia Ujfalussy; Anita Kurys; Enikő Kubinyi; Márta Gácsi; Zsófia Virányi (Royal Society Open Science, 2017)
Socialized wolves' relationship with humans is a much debated, but important question in light of dog domestication. Earlier findings reported no attachment to the caretaker at four months of age in a Strange Situation Test, while recently attachment to the caretaker was reported at a few weeks of age in a similar paradigm. To explore wolf–human relationship, we analysed behaviours of hand reared, extensively socialized wolves towards four visitor types: foster-parents, close acquaintances, persons met once before, and complete strangers during a greeting episode. As hypothesized, in the greeting context subjects showed more intense and friendly behaviour towards foster-parents, than other visitor types, which may reflect familiarity and affinity. However, differences were more pronounced in the group situation (at six months of age) than in the individual situation (at 12 and 24 months), suggesting that unique status of foster parents may become less distinct as wolves get older, while exploration of novel social agents is expressed more with older age. Fear related behaviour patterns were only found in the individual situation, mainly displayed towards strangers. We showed that, in case of extensively socialized wolves, distinctive affiliation and affinity towards the foster parent prevails into adulthood.